IMPLEMENTASI GERDU KEMPLING DI KELURAHAN ROWOSARI KECAMATAN TEMBALANG KOTA SEMARANG 2011 - Nugroho, Yanuar Widi; Subowo, Ari; Rengga, Aloysius (Journal of Public Policy and Management Review, 2014)
Poverty is a complex problem that requires integrated and sustainable handling. In order to eradicate poverty in Semarang, the municipality government carries out a program called â€œGerdu Kemplingâ€ which stands for Integrated Program on Health, Economy, Education, Infrastructure, and Environment. Â The implementation of â€œGerdu Kemplingâ€ program in Rowosari village includes surveying poor citizen, counseling with the local community, SKPD personnel, and university experts, identifying and mapping the problem(s), prioritizing programs and aims, carrying out programs, monitoring programs, and evaluating programs, as well as understanding factors that promote or hinder â€œGerdu Kemplingâ€ program. Â  This research uses the qualitative descriptive approach as its analytical unit. The data are collected from questionnaires, interviews, documentations, and observations. Â Results show that â€œGerdu Kemplingâ€ program in Rowosari village is not optimum as there are many problem in its implementation, such as miss-matches between programs and their purpose in the community, and lack of synchronization between programs and their supporting activities. Factors that affect these include; lack of socialization, unverified number of poor citizen, and lack of commitment from program personnel to make the program successful.